Changing the criteria applied to acceleration and deceleration efforts changes the types of player actions detected - Ellens, S.; Carey, D.; Gastin, P.; Varley, M. C. (Science and Medicine in Football, 2024)
This study identified and profiled the types of player actions of Australian football players executed during high acceleration and/or deceleration efforts and identified how the duration exceeding the acceleration or deceleration threshold influenced the identified executed player actions. The commencing speed of the acceleration and deceleration efforts were also assessed. Acceleration and deceleration efforts of 22 Australian football players monitored with a 10-Hz GNSS device across two matches were analysed. Synchronised video footage of the matches was used to identify the player actions executed during acceleration and deceleration efforts. Linear mixed models were conducted to examine the relationship between commencing speed, player action, and duration exceeding the effort threshold. `Linear movement` and `jump` were the most frequently executed player actions for high accelerations and `stop` and `being tackled` for high decelerations. Significant differences were observed in commencing speed between player actions for the high deceleration efforts. Furthermore, it was found that a higher commencing speed was associated with an increased duration exceeding the deceleration threshold. These findings will help practitioners and researchers with selecting minimum-duration criteria for acceleration and deceleration efforts and provide an understanding of the types of player actions executed during these efforts.